A comparative study on prevalence of uropathogens and their antibiogram in diabetics and non-diabetics attending a tertiary care hospital - Anne, Tanmay; Suryadevara, Vijayadurga; B., Anuradha (International Journal of Research in Medical Sciences, 2024)
Background: Urinary tract infection (UTI) is a significant problem in both diabetics and non-diabetics. High glucose may create a culture medium for growth of the virulent organisms. Diabetics are at greater risk for developing complications of UTI. Extensive and improper use of antibiotics has caused widespread anti-microbial resistance among uro-pathogens. Indiscriminate use of antibiotics during Covid-19 pandemic might lead to more resistant uro-pathogens which might further complicate the treatment of UTI. This study will help to determine resistance patterns of common uro-pathogens, which is essential for proper patient care. Methods: Clean voided midstream urine samples were collected from 91 patients (67 diabetic and 24 non-diabetic). Urine cultures were performed using semi-quantitative technique and pathogens were identified using phenotypic methods. Those with colony forming units (CFU) ≥105 CFU/ml were subjected to antibiotic sensitivity testing by Kirby-Bauer disk diffusion method and the isolates were classified as sensitive, and resistant according to CLSI guidelines. Results: E. coli (53.84%) and Enterococci (29.67%) were the most commonly isolated pathogens of UTI in both diabetics and non-diabetics. E. coli resistance to imipenem was statistically more in diabetics when compared to non-diabetics (p=0.012). Resistance patterns of other organisms were similar in both the groups. Conclusions: E. coli was the most common pathogen isolated in both groups followed by Enterococci and Klebsiella. Diabetics showed statistically significant higher resistance (100%) to imepenem than non-diabetics. Other organisms isolated in this study did not show any statistically significant difference in their antibiogram.